2013
DOI: 10.1136/bmjopen-2012-002053
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the WHO Violence Against Women instrument in a female population-based sample in Sweden: a cross-sectional survey

Abstract: ObjectiveTo explore psychometric properties of the Violence Against Women instrument in a randomly selected national sample of women (N=573) aged 18–65 years and residing in Sweden.DesignCross-sectional survey study.SettingSweden.ParticipantsA postal survey was sent to 1006 women between January and March 2009, during which 624 women (62%) returned the questionnaire. 51 women who did not answer any of the violence items were excluded from the analyses, resulting in a final sample of 573 women.Primary and secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 34 publications
(19 reference statements)
6
57
0
Order By: Relevance
“…Future research should focus on a pilot study for clinical application with feedback from both patients and clinicians regarding usefulness in the physical therapy setting for female patients. [13][14][15] …”
Section: Resultsmentioning
confidence: 99%
“…Future research should focus on a pilot study for clinical application with feedback from both patients and clinicians regarding usefulness in the physical therapy setting for female patients. [13][14][15] …”
Section: Resultsmentioning
confidence: 99%
“…This means that the subjective experience of intimate partner violence is different for men and women but that they perpetrate similar acts of physical violence (Straus, 2012). Likewise, when investigating the psychometric properties of the VAWI among men and women, Nybergh found that the conceptual map for VAWI was different between the sexes (Nybergh et al, 2012;Nybergh et al, 2013a;Nybergh et al, 2013b). It was not as easy to see clear boundaries between the concepts of sexual, physical and emotional violence for men as for women.…”
Section: Lack Of Contextmentioning
confidence: 99%
“…However, the differences were only significant for emotional violence, both among men (VAWI=30.6% and NorAQ =10.2%) and women (VAWI=17.1%, NorAQ =2.6%). The differences could largely be attributed to two items concerning milder forms of emotional violence on VAWI that did not have any corresponding item in NorAQ (Nybergh et al, 2012(Nybergh et al, , 2013b. The large discrepancy between prevalence rates serves to illustrate that prevalence rates are largely dependent on the definitions and measurements used.…”
Section: Defining Labelling and Operationalizing Violencementioning
confidence: 99%
See 1 more Smart Citation
“…To further Cronbach's alpha comparison, we used Nyberg's study that was conducted with randomly selected male participants [9]. This study used the Violence against Women Instrument (VAWI).…”
Section: Compare and Contrastmentioning
confidence: 99%